Orta öğretim fizik öğretmeni yetiştirilmesinde mesleki yaşam hikayelerinin araştırılması - Çeltik, Taylan (My University, 2004)
ORTAÖĞRETİM FİZİK ÖĞRETMENİ YETİŞTİRİLMESİNDE MESLEKİ YAŞAM HİKAYELERİNİN ARAŞTIRILMASI Bilim ve teknolojinin hızla ilerlediği dünyamızda bir ülkenin kalkınması, toplumun ilerlemesi ve modern bir sanayi ülkesi olması teknik insan gücüyle mümkündür. Günlük yaşamdaki teknolojik ve bilimsel gelişmelerde, öğretmenlerin önemli bir etkisi vardır. Öğretmenlerin yetiştiriği öğrenciler bu buluşları gerçekleştiren bireylerdir. Bu da öğretmenlerin şu anda meslekleri ile ilgili konulara olan değişik tutumları için yaşam hikayelerini inceleme metodu ile çocukluk dönemlerinin ortak ve farklı kriterlerini incelemenin önemine işaret eder. Fizik pozitif bilimlerde en çok ağırlığı duyulan ve aynı zamanda toplumun hayat standardını etkileyen fen bilimidir. Bu yüzden diğer öğretmenlik alanlarında olduğu gibi fizik öğretmenliği ile ilgili yapılacak yeni yaklaşımlar hayati bir önem teşkil etmektedir. Fizik öğretiminin öneminin gün geçtikçe arttığı bilincinden hareketle bu alana yönelik çalışmalar, fizik eğitiminin kalitesinin yükseltilmesi anlamında bir ihtiyaç olarak belirmektedir. Fizik eğitimini gerçekleştirecek öğretmen adaylarının eğitiminde amaçların istenen düzeyde gerçekleştirilebilmesi için, çocukluk döneminde yaşadıkları parametrelerden kaynaklanan ve şu anki mesleğe karşı oluşturacakları tutumları besleyen altbaşlıkların önceden tespiti ve buna göre gruplar oluşturarak düzeltici çalışmaların yapılması önemlidir. Mesleki yaşam hikayelerini inceleme de bu yöntem ve tekniklerden biridir. Bu araştırmada, fizik öğretmenlerinin ve öğretmen adaylarının çocukluk dönemleri mesleki yaşam hikayelerini inceleme metodu kullanılmıştır. Bu parametrelerin öğretmenliğe karşı tutumlarını nasıl farklılaştırdığı incelenmiştir. Araştırmanın problem cümlesini Çocukluk dönemi parametrelerine göre ortak özellikler taşıyan öğretmen ya da öğretmen adaylarının mesleki tutum dereceleri farklılaşmakta mıdır? Sorusu oluşturmaktadır. Araştırma 2003-2004 eğitim-öğretim yılında, İstanbul ilinin çeşitli ilçelerindeki liselerde ve Marmara Üniversitesi'nde yapılmıştır. Araştırmaya bu okullarda görev yapan 42 fizik öğretmenleri ile 72 fizik öğretmenliği bölümü son sınıf öğrencisi katılmıştır. Verilerin istatistiksel olarak değerlendirilmesinde tek yönlü varyans analizi (ANOVA) ve Scheffe Testi'nden faydalanılmıştır. Araştırmada, elde edilen bulgulara dayanarak çocukluk dönemi parametrelerini oluşturan yaşanılan şehir, ilkokul yapısı, sınıf öğretmeni, anne, baba, aile, vb. konularında farklı özellikler taşıyan öğretmen ya da öğretmen adaylarının öğretmenlik mesleğine karşı tutum puanları da farklılaşmıştır sonucu çıkarılmıştır. Bu sonuca dayanılarak öneriler getirilmiştir.

SEARCHING TEACHERS' LIFE HISTORIES IN PHYSICS EDUCATION In the world of rapidly developing science and technology, social and industrial development of a country is dependent upon the technical and intellectual human resources. Teachers have the most pronounced impacts on technological and scientific development. Selecting true teachers for human resources and preparing specific educations for them is important to compose attitude change on being teacher as an occupation. In the class of physics education it is observable that the physics teacher has negative attitude and positive attitude to theorical part of physics, practical part of physics, theoric part of physics education or experimental part of physics education. Life history as a research method is adapted for investigating child hood of the teachers and the prospective teachers. Results are used to obtain common and different part of childhood parameters. Due to importance of physics education studies about this field, increasing the quality of physics education is a necessity. Explaining the broad expanse of the techniques of life histories and family histories, how these two techniques are complementary and how they differ from the 'cross-sectional' approach implicit in much social science research. An account is given of the sporadic development and use in the social sciences of life and family histories. Three basic perspectives on the life and family history methods - the 'realist', the 'cultural' and the 'narrative' - are introduced. Their current development and applications in an international context are surveyed. Methodological steps raised by the three approaches to biographical research. Modes of data collection for both biographies and family histories have seen much advancement and standardization in recent years but agreed methods of analysis still await development. The realist approach sees both life stories and family histories as means of collecting factual empirical materia1. The goal of analysis is the generation of concepts through induction and grounded theory techniques. The final step of investigating life histories summarizes the features of the three approaches to biographical research and speculates about the genesis of an overarching biographical perspective. In order to construct their biography, the individual must take account of their past history and its working through the present to an anticipated future. The 'account taking' includes an estimation of preceding social structures, their future evolution and the person's own placement in them. This 'embedded ness' in time and structure is necessary for an individual's own sense of autobiography. Biographical analysis requires an analogous 'embedded ness'. The adoption of a biographical perspective in social research implies transcending barriers of self/ society and past/ present/ future. This transcendent nature of biographical research opens prospects for a significant advance in educational conceptualization. (Miller, 1998) In this research, life history account as a research method was used in physics lessons. The main argument of the research was What are the common and different childhood parameters in the group of teachers or prospective teachers that has the same attitude level to being teacher as an occupation? The research took place in different types of high schools in Istanbul in 2003-2004 academic year. Research participants were 42 physics teachers and 78 prospective teachers. Prospective teachers were the last class students of Marmara University Department of Physics Education.
Keywords: Eğitim; Öğretmenler; Öğretmenler, Yetiştirilmesi_Türkiye; Öğretmenlerin mesleki eğitimi